(untitled) (UUM Journal of Legal Studies, 2023)
Additive manufacturing in the field of tissue engineering has evolved rapidly over the past few decades. 3D bioprinting is an extended application of additive manufacturing that involves the building of tissue or organ in a layer-by-layer manner using a bioprinter via instructions from computer graphic software. 3D bioprinting technology offers promise in the transformation of healthcare sectors. Consequently, disputes regarding commercial use of 3D bioprinting, in particular on intellectual property rights will arise. Patent ownership and registration of bioprinting products and processes pose issues of ethics. The copyrighted works of 3D bioprinting software pose risks of copyright infringement. Besides, there is also a question of whether the marks and brand of 3D bioprinters can be protected as trademarks. The main objective of this study is to analyse how existing intellectual property laws in Malaysia can be utilized to protect 3D bioprinting technology intellectual property rights. The qualitative method is employed in this study, in particular, content analysis of journal articles, books, international conventions, directives, statutes and court cases. Semi-structured interviews with two respondents from relevant ministries were conducted to achieve the objectives of this study. Additionally, a comparative study of legal frameworks in the United States and Europe is adopted to examine intellectual property rights on the international stage. The study revealed that 3D bioprinting products and processes are patentable under the Patents Act 1983; however, ethical and morality issues are challenges in granting protection. Apart from that, copyright can protect computeraided bioprinting design software and programs under the Copyright Act 1987 and the marks and brand of 3D bioprinting products can be protected under the Trademark Act 2019. The findings of this study will expose the potential in commercialization of 3D bioprinting among industry players and propose improvements to the current regulatory framework of 3D bioprinting related to intellectual property rights.